โปรแกรมเสริมสร้างภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษามหาสารคาม เขต 1 - สารพล, อุมาภรณ์; เรืองมนตรี, กาญจน์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 5 No 1 (2568): มกราคม – เมษายน 2568, 2025)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพที่เป็นจริง สภาพที่คาดหวัง และความต้องการจำเป็น และ 2) สร้างและประเมินโปรแกรมเสริมสร้างภาวะผู้นำทางวิชาการของ ผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษามหาสารคาม เขต 1 เป็นการวิจัยแบบผสมผสาน กลุ่มตัวอย่าง ได้แก่ ผู้บริหารสถานศึกษา รองผู้บริหารสถานศึกษา และรักษาการในตำแหน่งผู้อำนวยการสถานศึกษา จำนวน 135 คน ได้มาโดยการสุ่มแบบแบ่งชั้นภูมิ และมีกลุ่มผู้ให้ข้อมูล จำนวน 3 คน เครื่องมือวิจัย ได้แก่ แบบสอบถาม แบบสัมภาษณ์ และแบบประเมินความเหมาะสม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ประกอบด้วย ร้อยละ ค่าเฉลี่ยเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน และดัชนีความต้องการจำเป็น ผลการวิจัยพบว่า 1) สภาพที่เป็นจริงของภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา โดยรวมอยู่ในระดับปานกลาง และ สภาพที่พึ่งประสงค์ฯ โดยรวมอยู่ในระดับมากที่สุด ส่วนความต้องการจำเป็นในการเสริมสร้างฯ เรียงลำดับจากมากไปน้อย ได้แก่ การนิเทศและประเมินผลด้านการสอน การส่งเสริมบรรยากาศการเรียนการสอน การบริหารหลักสูตร และการกำหนดเป้าหมายของโรงเรียนตามลำดับ และ 2) โปรแกรมเสริมสร้างภาวะผู้นำทางวิชาการฯ ประกอบด้วย หลักการ วัตถุประสงค์ เนื้อหา วิธีการพัฒนา และการวัดและประเมินผล ซึ่งเนื้อหาของโปรแกรมฯ ประกอบด้วย 4 Module ได้แก่ การกำหนดเป้าหมายของโรงเรียน การนิเทศและประเมินผลด้านการสอน การส่งเสริมบรรยากาศการเรียนการสอน และการบริหารหลักสูตร ส่วนผลการประเมินความเหมาะสมและความเป็นไปได้ของโปรแกรมอยู่ในระดับมากที่สุดทั้ง 2 รายการ The objectives of this research article were: 1) to study the current conditions, the desired conditions, and the needs, and 2) to develop and evaluate a program for enhancing Instructional leadership among school administrators under the jurisdiction of the Maha Sarakham Primary Educational Service Area Office 1. This research employed a mixed-methods approach. The sample group consisted of 135 participants, including school administrators, deputy school administrators, and acting school directors, selected through stratified random sampling. In addition, there were 3 key informants. The research instruments included questionnaires, interview forms, and suitability assessment forms. The statistics used for data analysis comprised percentage, mean, standard deviation, and the Modified Priority Needs Index (PNI modified ). The research findings revealed that: 1) the current state of Instructional leadership among school administrators was at a moderate level overall, while the desired condition was at the highest level. The prioritized needs for enhancing Instructional leadership, in descending order, were: supervision and evaluation of teaching, promoting a conducive teaching and learning environment, curriculum management, and setting school goals; and 2) the developed program for enhancing Instructional leadership consisted of principles, objectives, content, development methods, and evaluation methods. The content of the program comprised four modules: setting school goals, supervision and evaluation of teaching, promoting a conducive teaching and learning environment, and curriculum management. The results of the evaluation of the program's suitability and feasibility were found to be at the highest level in both aspects.